THE USAGE OF UBVRI FILTERS AND SKY BRIGHTNESS MEASUREMENT (Study on 26 May 2021 Total Lunar Eclipse at ITERA Lampung Astronomical Observatory ) - Hendra Agus Prastyo; Khabib Suraya; Singgih Prana Putra; Aditya Abdilah Yusuf; Izatul Hafizah; Adhitya Oktaviandra; Aziz Nugrahamuda Khagahdo; M R Kurniawan; Gabriella Maharani; Ababil Silahuddin (Fakultas Syari'ah dan Hukum UIN Walisongo, 2021)
On May 26, 2021, the ITERA Lampung Astronomical Observatory (OAIL) got the opportunity to watch the Total Lunar Eclipse (TLE). The observations had two goals: determining the most efficient filter for observing the Penumbral Lunar Eclipse (PLE) and determining the influence of TLE phenomena on sky brightness. The acquired picture data is analyzed using the photometric approach. Six sample points are utilized to calculate the magnitude of the PLE. According to the findings, the blue filter is the generally ideal filter for detecting PLE. Tycho crater had the greatest magnitude of -18.1 while mare Imbrium had the highest magnitude of -17.2. When determining the intensity of the crater and mare, this value is impacted by various parameters, including the duration of the integration period and the aperture radius. As a result, this number still has to be adjusted to the full moon's intensity. The results of SQM measurements of the sky's brightness form a light curve pattern that declines during the umbra phase and continues to diminish until the Moon departs the Earth's penumbra. This shows that the value of sky brightness increases or the sky becomes significantly darker during the total phase, while the Moon's skyglow diminishes during TLE.